Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm sure it's staring at me, but how does one solve this?

$$ (y')^2 + y = xy' $$

Thanks.

share|improve this question
1  
That's Clairut's equation. Wolfram alpha gives a clean solution step by step in this case, just click the 'show steps' button. –  H. M. Šiljak Dec 19 '11 at 16:34
    
That should have been Clairaut, actually. –  H. M. Šiljak Dec 19 '11 at 16:35
    
One solution is $y = x-1$? –  AD. Dec 19 '11 at 16:44
1  
@H.M.Šiljak: I think you meant this one. –  Gigili Dec 19 '11 at 16:49
    
Ok, got it. Differentiating both sides wrt x 2y'y'' + y' = y' + xy'' i.e., y''(2y'-x) = 0 which can now just be solved for each case in turn, y'' = 0 and 2y' = x Thanks everyone. –  Simon S Dec 19 '11 at 16:50

1 Answer 1

Differentiating both sides with respect to x:

$$2y^\prime y^{\prime\prime}+y^\prime =y^\prime+xy^{\prime\prime}$$

i.e., $y^{\prime\prime}(2y^\prime −x)=0$ which can now just be solved for each case in turn, $y^{\prime\prime}=0$ and $2y^\prime=x$

Thanks everyone.

share|improve this answer
    
Note that not every solution to $y'' = 0$ and $2y' = x$ automatically works because the differentiation step is not reversible. But it's easy to plug the solutions to those into the original equation and find out which solutions do work. –  Zarrax Dec 20 '11 at 1:54

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.